Deteksi dan Evaluasi Keragaman Genetika Candidatus Liberibacter asiaticus sebagai Penyebab Penyakit Huanglongbing di Indonesia Berdasarkan Gen β-operon - Muhammad Rizal; Kikin Hamzah Mutaqin; Gede Suastika (Jurnal Fitopatologi Indonesia, 2016)
Huanglongbing also known in Indonesia as citrus vein phloem degeneration (CVPD) is a devastating disease in citrus plantation worldwide, especially in Asia, Africa, and America. In Asian countries including Indonesia, Candidatus Liberibacter asiaticus (CLas) has been confirmed as the causal agent of huanglongbing disease on citrus. Distribution of CLas in Indonesia has been reported in West Borneo, East Nusa Tenggara, Bali, Yogyakarta, Central Java and East Java.  The purpose of this study was to detect CLas in several Indonesia’s citrus plantations that has not and has been reported previously and to study its genetic diversity and their relationship. DNA of plant samples, i.e. citrus leaves, was extracted using CTAB method and CLas was amplified using PCR with the A2/J5 primer pair. DNA amplification results showed that infection of CLas was positively detected from samples from Bogor and Cibodas (West Java), Tuban and Jember (East Java), as well as Katung, Bayung Gede, Kerta, and Pancasari (Bali). Alignment of nucleotide sequences from positive samples showed that their ribosomal protein β-operon has high similiarity to that of CLas OK901 originated from Okinawa (Japan). Isolates of CLas originated from Bogor, Cibodas, Tuban, Jember, and Katung have been known to be identical to other CLas of Indonesian origins reported earlier.  Isolates of CLas originated from Bayung Gede, Pancasari, and Kerta have single nucleotide polymorphisms at 6 points of bases of the 539 total bases compared in their conservative regions, although only 3 of the 6 bases could affect their amino acid sequences.